Study of Creating Functional Disorder Ratio Scale for Locomotor System Restrictions Abstract - Seviçin, Sedat (The Bulletin of Legal Medicine, 2021)
Objective: In this study, to emphasize the importance of evaluating locomotor system limitations in terms of functional impairment or loss of function in injury, traffic accident and occupational accident reports and to contribute to the development and updating of the existing Guidelines for wounding offenses. The aim of the study is to develop a new scale that evaluates the loss of the organ as a percentage of its function in locomotor system limitations.Methods: The patients who applied to the forensic medicine department and were evaluated for the impairment of the locomotor system due to injury were considered as impaired or lost their function. Using the scale we developed and compared with the report results made by our department. Results: 70 cases included in our study were re-evaluated according to the new scale. It was seen that different results occurred in 5 cases (7.1%). When these cases were examined according to the new scale, it was seen in the evaluation that in 3 cases the limitations were very close to the 10% limit of loss in terms of organ.Conclusions: A new scale was created by using the scale of disability in order to have standardized objective criteria when evaluating the locomotor system limitations and to facilitate the physicians, which are frequently encountered in forensic medical practices. Therefore, due to limitations in organs the percentage of functional impairment was found to be more important, especially at borderline levels of functional impairment (%10) and a standardized scale should be used.
Keywords: Forensic medicine; impairment; loss; limitation; guidelines